Optimization of the Electrodeposition Parameters to Improve the Stoichiometry of In2S3 Films for Solar Applications Using the Taguchi Method. (30th April 2014) - Mughal, Maqsood Ali; Newell, M. Jason; Vangilder, Joshua; Thapa, Shyam; Wood, Kayla; Engelken, Robert; Carroll, B. Ross; Johnson, J. Bruce
Abstract : Properties of electrodeposited semiconductor thin films are dependent upon the electrolyte composition, plating time, and temperature as well as the current density and the nature of the substrate. In this study, the influence of the electrodeposition parameters such as deposition voltage, deposition time, composition of solution, and deposition temperature upon the properties of In2 S3 films was analyzed by the Taguchi Method. According to Taguchi analysis, the interaction between deposition voltage and deposition time was significant. Deposition voltage had the largest impact upon the stoichiometry of In2 S3 films and deposition temperature had the least impact. The stoichiometric ratios between sulfur and indium (S/In: 3/2) obtained from experiments performed with optimized electrodeposition parameters were in agreement with predicted values from the Taguchi Method. The experiments were carried out according to Taguchi orthogonal array L27 (3 ^ 4 ) design of experiments (DOE). Approximately 600 nm thick In2 S3 films were electrodeposited from an organic bath (ethylene glycol-based) containing indium chloride (InCl3 ), sodium chloride (NaCl), and sodium thiosulfate (Na2 S2 O3 ·5H2 O), the latter used as an additional sulfur source along with elemental sulfur (S). An X-ray diffractometer (XRD), energy dispersive X-ray spectroscopy (EDS) unit, and scanning electron microscope (SEM) were, respectively, used to analyze the phases, elemental composition, and morphology of the electrodeposited In2 S3 films.